Seasonality and Meteorological Factors Associated With Different Hand, Foot, and Mouth Disease: Serotype-Specific Analysis From 2010 to 2018 in Zhejiang Province, China - Chen, Yijuan; Sun, Wanwan; Ling, Feng; Sun, Jimin; Cao, Yanli; Chen, Zhiping; Miao, Ziping (Frontiers in Microbiology, 2022)
Background: Hand-foot-mouth disease (HFMD) is caused by a group of enteroviruses (EV) and had a high incidence in children and some subtypes had high mortalities in children. The subtypes of HFMD had difference incidence across seasons. Thereby, we suspect that the infection of HFMD is varied by meteorological factors. However, the study examining the serotype-specific associations between meteorological factors and HFMD incidence were rare. Methods: We obtained all HFMD cases occurred during 1 January 2010 to 31 December 2018 in Zhejiang Province from the China Information System for Disease Control and Prevention (CISDCP). Daily meteorological data for Zhejiang Province were provided by the China Methodological Data Sharing Service System and linked to HFMD cases based on their residential addresses and date of onset. The associations between meteorological factors and HFMDs were examined using distributed lag non-linear models (DLNMs) for each serotype. Results: Overall, the incidences of all HFMD cases were increasing in study years, while the number of severe and fatality cases were a decreasing. The dominant serotypes varied by study years. The association between temperature and the incidence of CVA16 or EV71 serotypes both showed an inverted U-shape association. The risk ratio for CVA16 was increasing when temperature is 11-25℃, maximum RR at 18℃ and humidity above 77% can promote the occurrence with CVA16, and temperature between 11-32℃ with the maximum RR at 21℃ and relative humidity above 77% are risk conditions of the occurrence of HFMD associated with EV71. For other enteroviruses causing HFMD, temperature above 11℃ and humidity above 76% have a risk effect. CVA16, EV71 and all enteroviruses of HFMD have the maximum effect at lag day 0, temperature is 35℃, 34℃ and 33℃ respectively, while other enteroviruses of HFMD other than EV71 and CVA16 has the maximum effect when the temperature is 33℃ and the lag time is 7 days. Conclusion: This study shows that meteorological factors have an effect on the occurrence of different HFMD serotypes. Local control strategies for public health should be taken in time to prevent and reduce the risk of HFMD when the weather condition of warm and humid climate.